Free Trade Area of the Americas by 2005 : the new direction. - RODRIGUEZ, Luis Alberto (1996)
Focuses on the readiness of the Latin American and Caribbean countries to obtain maximum benefits through preparation for effective negotiations and to take advantage of the benefits of free trade. Discusses problems that arise when states of varying levels of size and development seek to jointly enter into trade agreements, and the capacity of the private sector to access the means to prepare itself to fully participate in the new hemispheric environment.